Perbedaan Kesejahteraan Siswa Pada SMA Negeri Asrama dan Bukan Asrama di Kota Malang - winurini, sulis (Jurnal Aspirasi, 2018)
Boarding schools have their own peculiarities. Students in boarding schools will spend all their time in schools and dormitories, while students in day schools still have experience with their families and neighborhoods. This difference in experience will lead to differing perception, so it is assumed that there are differences in school well being in the two school models. The purpose of this study is to find out whether or not there is a difference in school well being for students in boarding public high schools (SMAN) with day public high schools (SMAN) in Malang. Using quantitative method. The research was conducted in Malang City on July 19, 2018. The total participants involved in this study were 186 people, consisting of 89 students from day high schools and 97 students from boarding high school. The results of the study using the t-test showed a significant difference in the average score in the variable school well being between boarding high school students and day high school students (t= 5.29; p <0.05). The average score of a school well being at boarding school is higher than day school. Viewed from its aspect, it was found a significant difference in scores significantly on the aspect of having, not found a difference in the average score significantly on the love aspect, found the difference in average scores was significantly on the aspect of being. Judging from the average score of each aspect, the boarding high school students have an average score of the aspect of the school well being higher than the day high school students. That is, if viewed on a per-aspect basis of school well being, boarding high school students feel better than day high school students. AbstrakSekolah asrama memiliki kekhasan tersendiri. Siswa yang berada di sekolah asrama akan menghabiskan seluruh waktunya di sekolah dan asrama, sementara siswa pada sekolah bukan asrama masih memiliki pengalaman dengan keluarga dan lingkungan tempat tinggalnya. Perbedaan pengalaman ini akan menimbulkan perbedaan penilaian sehingga diasumsikan terjadi perbedaan kesejahteraan siswa pada kedua model sekolah tersebut. Tujuan dari penelitian ini adalah untuk mengetahui ada atau tidaknya perbedaan kesejahteraan siswa yang berada di SMA Negeri (SMAN) asrama dengan SMA Negeri (SMAN) bukan asrama di Kota Malang. Penelitian ini menggunakan metode kuantitatif di Kota Malang pada tanggal 19 hingga 26 Juli 2018. Total partisipan yang digunakan dalam penelitian ini adalah 186 orang, terdiri dari 89 siswa dari SMAN bukan asrama dan 97 siswa dari SMAN asrama. Hasil penelitian dengan menggunakan t-test menunjukkan perbedaan rata-rata skor secara signifikan pada variabel kesejahteraan siswa di sekolah antara siswa SMAN asrama dengan siswa SMAN bukan asrama (t = 5,29; p < 0,05). Rata-rata skor kesejahteraan siswa di SMAN asrama lebih tinggi dibanding SMAN bukan asrama. Dilihat dari aspeknya, ditemukan perbedaan rata-rata skor secara signifikan pada aspek kondisi sekolah, tidak ditemukan perbedaan rata-rata skor secara signifikan pada aspek hubungan sosial, ditemukan perbedaan rata-rata skor secara signifikan pada aspek pemenuhan diri. Dilihat dari rata-rata skor tiap aspeknya, siswa SMAN asrama memiliki rata-rata skor aspek kesejahteraan siswa di sekolah lebih tinggi dibanding siswa SMAN bukan asrama. Artinya, jika dilihat secara per aspek kesejahteraan siswa di sekolah, siswa SMAN asrama merasa lebih baik dibanding siswa SMAN bukan asrama.